NET CONSUMER OF RICE AND POVERTY IN INDONESIA: SIMULATION USING EQUIVALENT VARIATION - Respati, Wiena Maulidia; Gafara, Witra Ghaitsa; Izzati, Ridho Al (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
Indonesia’s domestic rice price has experienced a significantly increase when the global price of corps commodity decline. An increase in rice price from 2012 to 2015 had reached 30%. The most acute occurred on the first quarter of 2014 until the last quarter of 2015 that overtake 17%. Increase in domestic rice price will affect mostly to consumer welfare in Indonesia, because as we know, rice is one of the staple food for Indonesian people whom has inelastic demand.This paper uses National Socio-economics Survey (SUSENAS) year 2012 and 2014. We revisit McCulloch (2008) and used SUSENAS 2004 to calculate amount of agricultural household in Indonesia. The result of the author’s calculation there was a diminution from 46% in 2004 to 37% in 2012 on the amount of agricultural households in Indonesia. From the total of agricultural household, 19% are the rice-farming households. Surprisingly, 90% of Indonesia’s households are the net consumer whom bought the rice from the market. The result shows that 15% of the total net consumers are the rice-farming households and 10% of net consumers are poor households. This means that if there is an increasing in the price of rice, automatically this household will get influenced include the rice farmers who in fact is also as the rice producers.The authors conduct simulation to see the effect of the increase in the rice price towards consumptions that ultimately will alter poverty incidence. Simulation that has been performed uses equivalent variation method to calculate a changing on household consumption as the result of an increase in the rice prices. The result from the simulation of a increase in rice price shows that households in every quantile is affected, ceteris paribus. Authors also including Raskin as compensated consumption when there is an increase in rice prices. These findings suggest that, rice price should be stabilized in order to maintain the society’s welfare and government should establish pro-poor policy especially for food security to prevent the increasing of poverty incidence.  Keywords: rice price, poverty, rice farmer, equivalent variationJEL Code: I32, Q18